Bon appetit complete branding for restaurants, cafes and bakeries. (SendPoints Publishing Co., Ltd., 2018)
International and diverse in scope, Bon Appetit showcases establishments that have gone the extra mile, providing cohesive brand identities that make use of every possible advantage to strengthen their appeal. Branding for restaurants and other eateries provides unique opportunities for the designer or agency involved due to the wealth of potential collateral with which to promote and reinforce the brand. From printed material such as menus, business cards and to-go packaging, to uniforms, interiors and signage, the combined impact of a successful identity is only limited by vision. Dark and elegant industrial fantasies compete with bright, colorful pop suites and stark modern masterpieces to capture consumer loyalty in this comprehensive volume.